Antibody Response to SARS-CoV-2 Infection in Non Vaccinated Health Care Personnel - Khanam, Parvin Akter; Hassan, M Sawkat; Alam, Md Sohrab; Belal, Md Hasan; Rahman, Zeenat Farzana; Begum, Tanjima; Khan, AK Azad (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background: Antibodies (Abs) are produced by B cells after infection with the SARS/COVID-19 virus. The presence of neutralizing antibody is an indicator of protective immunity for most viral infections. But, we still don’t know how long and how effectively this immune protection will cover. Objectives: This study aimed to estimate the antibodies level in PCR-confirmed COVID-19 subjects in non vaccinated healthcare personnel. Methods: SARS-CoV-2 specific total Abs (IgG and IgM), IgG of nucleocapsid (N) protein and spike (S) protein levels were estimated using two clinically validated and widely used serological assays, detecting antibodies against the Total Antibody, nucleocapsid(N) and spike(S) proteins. Results: A total 130 subjects with PCR-confirmed SARSCoV- 2 infection were included in this study and all subjects were symptomatic and blood samples were collected between 3 to 24 weeks. Of all participants, about 52% were female and mean age was 43.2 years. The study found that the Total Abs, IgG of N protein and neutralizing Abs of S protein were developed 100%, 74.6% and 93.8% respectively. The study also found that the IgG titers of the N protein peaked at about 19 weeks after onset and decreased thereafter. The study also found that the neutralizing Abs of S protein were gradually increasing in the second phase of (9wks-19wks) weeks and in the third phase of (19wks -24wks) weeks after disease onset than compared to the first phase of weeks (3wks- 9wks) and it was significant (p<0.001). Conclusion: The study concluded that the antibodies, total Abs, IgG titer of N protein and neutralizing Abs of S protein were developed 100%, 74.6% and 93.8% respectively. The study also observed that IgG of N protein was decreasing within 19-24 weeks and neutralizing Abs of S protein peaked at 19-24 weeks after the onset of disease. J Bangladesh Coll Phys Surg 2022; 40: 191-196